Активізація людського потенціалу в умовах глобалізації економіки - Бортнік, Світлана Миколаївна; Bortnik, Svitlana M. (Луцький національний технічний університет, 2012)
Досліджуються питання визначення перспектив розвитку та покращення використання людського потенціалу з врахуванням сучасних реалій глобалізаційних процесів та їх впливу на показники і можливості регіонального людського розвитку. The questions of determination of prospects of development and improvement of the human potential using are investigated taking into account modern realities of the globalization processes and their influence on indexes and possibilities of the real human. It is proven that activating of the human potential using development should be done by its effective management on all levels. It was proposed the approaches regarding the human potential activation by means of its transformation into object of state administration.
Activating of the human potential in environment of the economy globalization
Keywords: людський потенціал; розвиток людського потенціалу; управління людським потенціалом; human potential; activization; human potential development; administration